Video assisted thoracoscopic surgery in the management of acute fibrinopurulent empyema in paediatric patients - Mitra, Arti S.; Nagdeve, Nilesh G.; Khatri, Simran R.; Chandak, Unmed A. (International Surgery Journal, 2020)
Background: Empyema is the presence of pus in the pleural space that usually follows an episode of pneumonia in pediatric age group. The aim of this study was to assess the efficacy of management of acute fibrinopurulent stage of empyema by early video assisted thoracoscopic surgery (VATS) in paediatric patients. Methods: The study was carried out at a tertiary care hospital in India. It was a prospective interventional observational study. The study included 40 children between age group 0-12 years attending the surgery in-patient department referred for further management of parapneumonic effusions who had clinical and radiological evidence of empyema and thoracocentesis confirmed purulent exudate in pleural cavity, were subjected to early VATS after thorough pre-operative workup. Results: The mean age was 7.22 years. Average operative time was 135.5 minutes. The mean duration of hospital stay was 7.5 days. Few complications were bleeding, superficial wound infection, bronchopleural fistula, pneumothorax, recurrence of empyema and incomplete expansion of lung. Conclusions: VATS facilitates the management of fibrinopurulent and organised pyogenic pleural empyema with less post-operative discomfort and complications and reduced hospital stay. However larger sample size study is required to come to a definitive conclusion.